PENGARUH PENAMBAHAN BIOCHAR TERHADAP PENURUNAN KADAR TOTAL PETROLEUM HYDROCARBON (TPH) PADA TANAH TERCEMAR MINYAK BUMI - Aryo Sasmita; Amalia Syakinah; Ulfatun Nisa (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Hydrocarbons are compounds produced as a result of the activities of the petroleum industry, which can pollute the soil and waters. Due to the amount of waste, biochar from agricultural waste could potentially be used as a soil amendment agent for hydrocarbon contamination. The high lignocellulose in oil palm shells and empty bunches makes them potential raw materials for biochar. The purpose of this study was to explore the effect of biochar application on petroleum-contaminated soil to reduce Total Petroleum Hydrocarbon (TPH) levels. In this study, the dosage of biochar was added to the soil contaminated with petroleum with a variation of 3%, 5%, and 7% (w/w) and control without the addition of biochar. The parameters analyzed were TPH levels by gravimetric method every week for four weeks. The results showed that the addition of biochar had an effect on the degradation of TPH. The greater the dose of biochar used, the higher the percentage of TPH degradation. The highest decrease in TPH levels occurred at the addition of biochar dose by 7%, where the empty shell was 60.65%, and empty bunches was 54.1% which was greater than without the addition of biochar by 32.79%.